Why biodiversity in Malaysia is underestimated? - Abdullah, M.T; Kumaran, Jayaraj Vijaya; Khan,, Faisal Anwarali; Mohd Azhar, Mohd Isham; Rovie Ryan Japnin, Jeffrine (2012)
Recent studies over wide geographical areas on selected taxa in Malaysia on their ecology morphology and genetics indicate that there are intraspecific differences within species and among populations. This paper highlights on the recent findings of possible new species and subspecies that are yet to be described that will increase the biodiversity in this country. Classical theory of biogeography of wildlife in Southeast Asia that the ancestral population originated from Asian mainland is also challenged based on our new mitochondrial genes evident.